Pengaruh Pendidikan Kesehatan Tentang Metode Amenorea Laktasi Terhadap Pengetahuan Dan Sikap Pada Ibu Primipara di Rumah Sakit Umum Teungku Peukan Tahun 2023 - Nurul Fauzi; Ika Damayanti Sipayung; Sri Rezeki (The Journal General Health and Pharmaceutical Sciences Research, 2023)
The Lactational Amenorrhoea Method (MAL) is a type of contraception that can be relied on for six months after giving birth, the mother's fertility period has not yet returned, breastfeeding exclusively is sufficient and does not use bottles to give milk to the baby. The aim is to determine the effect of health education about the lactation amenorrhea method on the knowledge and attitudes of primiparous mothers at Teungku Peukan General Hospital in 2023.The type of research used is quantitative research. Quantitative research is a type of research that produces discoveries that can be achieved (obtained) using statistical procedures or other methods of quantification (measurement) of a set of objects which usually aim to see a picture of phenomena that occur in a certain population. The aim of the researchers was to determine the effect of health education on the knowledge and attitudes of primiparous mothers towards the lactation amenorrhea method.The chi-square value was found to be 0.03 <0.05, which means that there is an influence on the mother's knowledge of the lactation amenorrhea method at Teungku Peukan Regional Hospital in 2023.